II. Meşrutiyet Dönemi Dozy Reddiyelerinde Yeni Tarih Anlayışı (Mucize ve Miraç Hâdisesinin Değerlendirilmesi) / The New Comprehension of History During The Second Institutional Period of Ottoman Era: The Impact of "Essai Sur L’histoire De L’islamisme" of Dozy - Yenilmez, Hasan; Üstün, İsmail Safa (Journal of History Culture and Art Research, 2016)
The New Comprehension of History During The Second Institutional Period of Ottoman Era: The Impact of "Essai Sur L’histoire De L’islamisme" of Dozy Abstract During the Second Constitutional Period of Ottoman era, the translation movement of positivist and materialist texts from the West affected a number of the Ottoman intellectuals. The effects of these ideological movements could clearly be seen in their works. Following these ideological changes, the Ottoman intellectual’s perceptions towards classical Islamic history has been completely changed. Also, during the constitutional period, the Islamic history literature seems to be demonstrating a different sense of historical approach. It is also observed that during the second constitutional period along with the increased translation activities from the West, Ottoman intellectuals started to accommodate “the scientific historiography” approach. In his translation of Essai Sur L’histoire De L’islamisme, Abdullah Cevdet translated the title as History of Islam and he called Dozy “a complete neutral” and “a product of reasoning”. The majority of Ottoman intellectuals gravely criticized Cevdet’s work at that time. This article describes the works which refuses the works of Cevdet and analyzes how they try to explain the concepts like “Miracle” and the “Mirac” which are difficult to describe with scientific method. In this context the works of Manastırlı İsmail Hakkı, Nevşehirli Hayreddin, Şehbenderzade Filibeli Ahmed Hilmi also examined. II. Meşrutiyet Dönemi Dozy Reddiyelerinde Yeni Tarih Anlayışı (Mucize ve Miraç Hadisesinin Değerlendirilmesi) Öz II. Meşrutiyet döneminde, Batı’dan pozitivizm ve biyolojik materyalizm eksenli metinlerin tercüme edilmeye başlanması, Osmanlı aydınının bu fikrî hareketten etkilenmesine sebep olmuştur. Buna göre Osmanlı aydınının Klasik İslam Tarihi anlayışı tamamen değişmiş, II. Meşrutiyet döneminde kaleme alınan İslam Tarihi eserlerinde yeni bir tarih anlayışı ortaya konulmuştur. II. Meşrutiyet döneminde artan tercüme faaliyetleriyle eş zamanlı olarak Osmanlı aydınında “Bilimsel tarihçilik” anlayışının benimsenmeye başladığını görmekteyiz. Abdullah Cevdet’in bir aydınlanma refleksiyle, Dozy’nin Essai Sur L’histoire De L’islamisme eserini “kat’iyyen bî taraf ve akl-ı selîm mahsûlü” olduğunu zikredip Târih-i İslâmiyet adıyla Türkçeye tercüme etmesi Osmanlı aydınının büyük tepkisine yol açmıştır. Bu makalede, Târih-i İslâmiyet’e reddiye olarak kaleme alınan eserlerde dönemin bilimsel tarihçilik anlayışından hareketle “Mucize” ve “Miraç” gibi konular ele alınacak, aynı zamanda bilimsel olarak açıklanması zor hadiselere Manastırlı İsmail Hakkı, Nevşehirli Hayreddin, Şehbenderzâde Filibeli Ahmed Hilmi’nin nasıl yaklaştıkları incelenecektir.